Haemodynamic changes to a midazolam–fentanyl–rocuronium protocol for pre‐hospital anaesthesia following return of spontaneous circulation after cardiac arrest. (15th February 2017) - Miller, M.; Groombridge, C. J.; Lyon, R.
Summary: Following the return of spontaneous circulation after out‐of‐hospital cardiac arrest, neurological dysfunction, airway or ventilatory compromise can impede transport to early percutaneous coronary intervention, necessitating pre‐hospital or emergency department anaesthesia to facilitate this procedure. There are no published reports of the ideal induction agents in these patients. We sought to describe haemodynamic changes associated with induction of anaesthesia using a midazolam (0.1 mg.kg −1 ), fentanyl (2 μg.kg −1 ) and rocuronium (1 mg.kg −1 ) regimen developed using expert opinion, and adherence to the protocol by our pre‐hospital teams. We performed a retrospective review of haemodynamic data recorded during induction of anaesthesia in patients following return of spontaneous circulation, over a 30‐month period. We analysed the changes in systolic blood pressure and heart rate using a repeated‐measures design, as well as the rate of new hypotension or hypertension. Sixty‐four patients had four consecutive measurements for analysis (one pre‐induction and three post‐induction). Systolic blood pressure at all three post‐induction measurements was significantly lower than the pre‐induction value. Heart rate did not differ between any time‐points. New episodes of hypotension (systolic pressure < 90 mmHg) occurred in four (6%) patients at the first measurement post‐induction (95%CI 2–15%) and 10 (16%) at the third measurement (95%CI 8–27%). Three patients (5%; 95%CI 1–13%) had a hypertensive response. The median (IQR[range]) dose of midazolam given at induction was 0.04 (0.03‐0.05 [0.01 to 0.10]) mg.kg −1 . Adherence to recommended fentanyl and rocuronium doses was high. Overall, systolic blood pressure was reduced following induction of anaesthesia, and systolic pressures < 90 mmHg occurred more often at measurements made later (up to 9 min) after induction. Changes in heart rate, and new hypertension were uncommon.